Pengaruh Fortifikasi Tepung Teripang Pasir (Holothuria Scabra) terhadap Karakteristik Organoleptik dan Kimia Kue Curuti - Tuba, Yulianti; Husain, Rahim; Suherman, Sutianto Pratama (The NIKe Journal, 2024)
This study aims to formulate and analyze the organoleptic and chemical characteristics of curuti cake fortified with sand sea cucumber flour. The treatment is the addition of 15 g, 20 g, and 25 g of sand sea cucumber flour to the curuti cake. The parameter tested is organoleptic characteristic including appearance, aroma, color, texture, and taste which is analyzed by using Kruskal-Wallis. The treatment with a significant effect is continued with Duncam advanced tes to see the difference in treatmen. chemical characteristic (moisture content, fat content, ash conten, protein content, carbohydrate content, and fiber content) is determined by using completely Randomized Design (CRD) and is analyzed by using ANOVA. The Duncam advanced test shows that the treatment of curuti cake formulation with different fortification of sand sea cucumber flour result in significantly different organoleptic characteristics, such as appearance, aroma, color, texture, and taste. The result of ANOVA test shows that the sand sea cucumber flour fortification treatment has an effect on the chemical characteristics of curuti cake ith the range of water content from 2.25 to 4.32%, ash content from 5.22 to 5.72%, fat content from 16.15 to 19.7%, protein content 15.51 to 22.72%, carabohydrate content from 49.34 to 58.49%, and fiber content from 0.14 to 0.30%. The best treatment, according to the panelists assessment, is the fortification of P2 sand sea cucumber flour for 20 grams which results in water content of 2.32%, protein content of 20.99%, ash content of 5.27%, fat content of 17.81%, carbohydrate content of 54.48%, and fiber content 0.16%.